Metodologia para análise da redução da capacidade de geração de energia em pequenas centrais hidrelétricas - Alessandra Aparecida de Lima (2018)
The energy produced by hydroelectric projects is directly dependent on the flow, the topographic at the site of the plant, as well as the efficiency of the adduction circuit and generator set. These variables and / or basic parameters, which can be determined methodologically in different ways, depending on the availability of data and the characteristics of the plant implantation site, may be influenced by different factors. The surface water availability of a given region can be influenced by the variation of the hydrometeorological regime, as well as by the variation of the different forms of land use and occupation. In plants that depend on the regularization of flows, the topographic difference may vary due to the depletion of the reservoir level and the time of year. The yields of the adduction circuit and generator set are dependent on the size and roughness of the walls of the water conduction systems as well as the geometry of the hydromechanical equipments, which can vary during the life of the installation, difficult to determine. In the vast majority of cases, impacts on the production and / or generation of a given hydroelectric plant are attributed only to the variation in surface water availability. However, the three factors cited can produce such impacts, independently or in groups. In view of the above, this work proposes a methodology based on the systemic analysis to evaluate and identify factors responsible for the supposed decay in the energy of hydroelectric power plants inserted in small hydrographic basins, including from the analysis of interventions related to the dynamics of groundwater and to the time evolution of the pressure loss in the low and high pressure pipes that make up the power generation system. As a result of this evaluation, applied to a hydrographic basin equipped with a set of Small Hydropower Plants, it was possible to verify that, in fact, several factors can intervene in generation capacity and that the change in local water availability is not always the only one responsible for these impacts. The results of the case study indicated the aging of the components of the adduction and generation system as the main responsible for the decrease in the generation capacity of the plants. Thus, based on internal roughness data from the pipelines of the mills' adduction circuit, it was possible to propose and evaluate an equation to allow the estimation of the aging factor and to associate the impacts on the generation.